Komunikasi Interpersonal Komunitas Sahabat Hijrah Dalam Menginternalisasi Kesadaran Beragama Dimensi Intelektual dan Ritual - Mahera, Nisa; Ilmi, Darul (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2026)
This study aims to analyze the role of interpersonal communication within the Sahabat Hijrah Community (KSH) in internalizing members’ religious awareness in intellectual and ritual dimensions. The study employed a qualitative field research approach using interviews, observations, and documentation, analyzed through the Miles and Huberman model with data triangulation. The findings reveal that interpersonal communication characterized by openness, empathy, supportiveness, positiveness, and equality plays a significant role in the internalization process. In the intellectual dimension, communication enhances understanding and religious thinking, although participation varies due to individual readiness. In contrast, the ritual dimension shows more stable patterns through continuous and collective worship practices, making internalization more effective. These findings contribute to the development of more contextual and effective interpersonal communication-based da’wah strategies.